The role of atomic scale investigation in the development of nanoscale materials for information storage applications. - Petford-Long, A; Larson, D; Cerezo, A; Portier, X; Shang, P; Ozkaya, D; Long, T; Clifton, P (2004)
It is well established that the response of devices based on the giant magnetoresistance (GMR) effect depends critically on film microstructure, with parameters such as interfacial abruptness, the roughness and waviness of the layers, and grain size being crucial. Such devices have applications in information storage systems, and are therefore of great technological interest as well as being of fundamental scientific interest. The layers must be studied at high spatial resolution if the microstructural parameters are to be characterized with sufficient detail to enable the effects of fabrication conditions on properties to be understood, and the techniques of high resolution electron microscopy, transmission electron microscopy chemical mapping, and atom probe microanalysis are ideally suited. This article describes the application of these techniques to a range of materials including spin valves, spin tunnel junctions, and GMR multilayers.